Exploring the Impact of Persuasion Knowledge and Parasocial Relationships on K-Pop Fans' Consumer Behavior in Indonesia - Khalid Abdul Hakim; Imam Salehudin (Journal of Enterprise and Development (JED), 2024)
Purpose: This study explores the impact of persuasion knowledge and parasocial relationships (PR) on electronic purchase intention, physical purchase intention, and electronic word-of-mouth (eWOM) in the context of K-Pop fanbases in Indonesia.Method: Data were collected through a survey using a questionnaire that measured variables such as persuasion knowledge, parasocial relationships, eWOM, and both electronic and physical purchase intentions. A total of 250 respondents, all of whom are followers of K-pop group fanbases on social media, were selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: The findings reveal that PK has a positive effect on E.PI, P.PI, and eWOM, contrary to the initial hypothesis that suggested a negative relationship. Consumers with higher PK tend to make more confident purchase decisions, both online and offline, and are more likely to engage in eWOM. Parasocial relationships also positively influence all three dependent variables, but the moderation effect of PR was generally insignificant, except for the relationship between PK and P.PI, where a negative moderation was observed.Novelty: This study fills the gap in existing literature by examining how eWOM and persuasion knowledge interact to influence K-Pop product purchases, a relationship that has been largely unexplored in the context of K-Pop fans who possess unique emotional attachments to their idols and products.